Answer:
Step-by-step explanation:
To find the roots of a quadratic equation, you need to solve the quadratic equation by using the quadratic formula.
OR
You can use the (Equation/Function) mode on the calculator.
[tex]\frac{-b+-\sqrt{b^{2} -4ac } }{2a} x \neq 0[/tex]
For this equation,
a = 3
b = 15
c = -5
X1 = [tex]\frac{-15+\sqrt{15^{2} -4(3)(-5) } }{2(3)} x \neq 0[/tex]
X2 = [tex]\frac{-15-\sqrt{15^{2} -4(3)(-5) } }{2(3)} x \neq 0[/tex]
Solving this on the calculator and you should get
X1 = [tex]\frac{=15+\sqrt{285} }{6}[/tex] X2 = [tex]\frac{=15-\sqrt{285} }{6}[/tex]
a, b, c = constants, where a ≠ 0
x = the unknown